Transcription factor SlBEL2 interferes with GOLDEN2‐LIKE and influences green shoulder formation in tomato fruits. (17th October 2022) - Niu, Xiao‐Lin; Li, Hong‐Li; Li, Rui; Liu, Gang‐Shuai; Peng, Zhen‐Zhen; Jia, Wen; Ji, Xiang; Zhu, Hong‐Liang; Zhu, Ben‐Zhong; Grierson, Donald; Giuliano, Giovanni; Luo, Yun‐Bo; et al.
SUMMARY: Chloroplasts play a crucial role in plant growth and fruit quality. However, the molecular mechanisms of chloroplast development are still poorly understood in fruits. In this study, we investigated the role of the transcription factor SlBEL2 (BEL1‐LIKE HOMEODOMAIN 2) in fruit of Solanum lycopersicum (tomato). Phenotypic analysis of SlBEL2 overexpression (OE‐ SlBEL2 ) and SlBEL2 knockout (KO‐ SlBEL2 ) plants revealed that SlBEL2 has the function of inhibiting green shoulder formation in tomato fruits by affecting the development of fruit chloroplasts. Transcriptome profiling revealed that the expression of chloroplast‐related genes such as SlGLK2 and SlLHCB1 changed significantly in the fruit of OE ‐SlBEL2 and KO‐ SlBEL2 plants. Further analysis showed that SlBEL2 could not only bind to the promoter of SlGLK2 to inhibit its transcription, but also interacted with the SlGLK2 protein to inhibit the transcriptional activity of SlGLK2 and its downstream target genes. SlGLK2 knockout (KO‐ SlGLK2 ) plants exhibited a complete absence of the green shoulder, which was consistent with the fruit phenotype of OE ‐SlBEL2 plants. SlBEL2 showed an expression gradient in fruits, in contrast with that reported for SlGLK2. In conclusion, our study reveals that SlBEL2 affects the formation of green shoulder in tomato fruits by negatively regulating the gradient expression of SlGLK2, thus providing new insights into the molecular mechanism of fruit green shoulder formation. Significance Statement: Chloroplasts play a crucial role in plant growth and fruit quality, but the molecular mechanisms underlying chloroplast development in fruits remain poorly understood. Here, our study reveals that SlBEL2 is expressed in a gradient in tomato fruits and affects the formation of the green shoulder in fruits by regulating chloroplast development, which provides new insights into the molecular mechanism of green shoulder formation in fruits.